Climate change impact and adaptation in agricultural systems (CABI climate change series, 2014)
This book contains 17 chapters focusing on the impacts of climate change on ecosystems, food security, water resources and economic stability. Strategies to develop sustainable systems that minimize impact on climate and/or mitigate the effects of human activity on climate change are also presented.